Injectable silk fibroin hydrogels with ionic strength and pH response for tissue engineering and regenerative medicine applications - Yan, Leping (2013)
Publicado em "Journal of Tissue Engineering and Regenerative Medicine", vol. 7, supp. 1 (2013)